The Peculiarities of Using Direct and Indirect Health Indicators When Evaluating the Dynamics of its Formation - O.V. Berdnyk; N.S. Polka; T.P. Skochko; O.V. Dobrianska; O.P. Rudnytska (Zaslavsky O.Yu., 2016)
To assess the health, there are traditionally used the indicators of morbidity, the incidence of violations of functional status and physical development of the body, i.e. indirect indicators that do not allow us to fully evaluate the level of population health. According to these parameters, the health of schoolchildren deteriorates: the number of healthy children reduces 1.8 times during training, at the same time, there is an almost twice increase in the proportion of children with chronic diseases, which indicates accumulation of chronic pathology in the pediatric population. For comprehensive health characteristics of the population, it is necessary to consider positive, i.e. direct health indicators, such as adaptive potential, the level of physical health and others, characterizing the state of adaptive reserves and integration capabilities of different systems. According to these indicators, we have found that the majority of primary schoolchildren had poor physical health, a third of pupils had average level, and only a tenth of primary schoolchildren had a high level of health. Much the same distribution in terms of physical health has been revealed in students of the middle school age. However, during the transition from middle to high school, the number of children with high levels of physical health begins to increase indicating an improve in adaptive capacities of the child's body with age. Thus, in the dynamics of learning in schools in terms of indirect and direct health indicators, there is a differently directed orientation of changes: on the one hand, accumulation of chronic pathology is detected in pediatric population, on the other - a synchronization of processes in the functioning of the various systems of the body that appears with age as the gradual increase in reserve capacities in children's body.